Zirconium-based surface treatment for welded aluminium alloys: overcoming phosphating limitations prior to organic coating - Ozyurt, Gulcan; Usta, Ibrahim (Taylor & Francis Ltd, 2026)
This study evaluates a Zirconium-based conversion coating as an eco-friendly alternative to conventional phosphating for welded aluminium alloys. Conventional phosphating often results in uneven coatings on high-silicon alloys and welded areas, reducing adhesion and corrosion resistance. The proposed chromium-, nickel-, and phosphate-free pretreatment contains hexafluorozirconic acid, organic silanes, stabilisers, and complexing agents, forming a thin, amorphous zirconium oxide layer that enhances paint adhesion and corrosion protection. The coating system was applied to 3103 and 5754 aluminium alloys and evaluated in two configurations: cataphoresis alone and a duplex system of cataphoresis followed by wet paint application. Compared to phosphating, salt spray tests and surface analyses showed that the Zirconium-based treatment provides more uniform coatings, better adhesion, and significantly improved corrosion resistance. These results demonstrate the method's technical effectiveness and environmental compliance, making it a promising surface preparation technique for automotive and industrial applications.
Keywords: Zirconium-based coating; aluminium alloys; surface pretreatment; cataphoresis; corrosion resistance; phosphate-free system